Analisis Kelayakan Usahatani Sayuran Hidroponik (Studi Kasus pada Usahatani Sayuran Hidroponik P4S Maura Farm di Kota Bekasi - Sri Kurniatiningsih; Muharam Muharam; I Putu Eka Wijaya (Peneliti.net, 2022)
P4S Maura Farm is one of the producers of hydroponic vegetables and also one of the pioneers in the development of hydroponic agriculture in Bekasi City. The types of vegetables cultivated are Pak Choy, kale, green spinach, red spinach, kailan, and lettuce. The purpose of this study is to analyze the income and analyze the feasibility of hydroponic vegetable farming at P4S Maura Farm. Analysis of the data used in the analysis of income and business feasibility by calculating the R/C Ratio, Break Event Point (BEP), and Payback Period (PP). The results showed that (1) P4S Maura Farm hydroponic vegetable farming income in one planting period on pakcoy commodity was Rp. 1,101,228, kale commodity Rp. 1,579,215, commodity green spinach Rp. 705,955, red spinach commodity Rp. 965,822, kailan commodity Rp. 882,212, and the commodity lettuce Rp. 1,068,545; (2) a. The R/C Ratio value obtained for each hydroponic vegetable commodity has reached more than one; b. The minimum number of P4S Maura Farm hydroponic vegetables that must be sold for each commodity is different, the minimum amount/highest break-even point obtained for your commodity lettuce is 196 kg, and the minimum price that must be charged for each commodity is also different, the minimum amount/highest break-even point The highest yield was obtained in the kailan commodity, which was Rp. 16,314/Kg; c. P4S Maura Farm hydroponic vegetable farming will experience a payback period of 4 years and 8 months based on a payback period of 4.8. So it can be concluded that P4S Maura Farm hydroponic vegetable farming is feasible to develop